Fenomena Hostess di Jepang dalam Drama Cabasuka Gakuen Karya Sutradara Takashi Kubota - Yogi Ardhaningsih, Ni Putu Ayu; Damayanti, Silvia; Anita Dewi, Ni Made Andry (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang, 2023)
"The Hostess Phenomenon in Japan in the Drama Cabasuka Gakuen by Director Takashi Kubota" is the title of this study. The purpose of this study is to learn more about the phenomenon, the duties of a hostess, and the efforts made by the hostess to deliver the best possible service. The descriptive analysis method was employed in this study. Service Theory, Semiotics Theory, and Sociology of Literature Theory are the theories utilized. According to the study's findings, it is known that the hostess phenomenon can be seen in three ways, 1) factors that cause someone to become a hostess, there are (1) bad financial conditions; (2) does not have an education degree; 2) the qualifications of a hostess; 3) the job of a hostess, there are (1) welcoming clients; (2) serving clients; (3) take the client out when finished visiting. A hostess makes the following efforts to give the best service: (1) maintaining an attractive appearance; (2) being adaptable in all circumstances; (3) listening to client complaints; (4) becoming familiar with the terms used in the cabaret club; and (5) fulfilling client requests outside the cabaret club. The findings of this study show that the desire of high school students to work as hostesses, which is thought to be an easy job to obtain and do, is actually not as easy as assumed. In order to keep their place, hosts must compete with one another.